2012
DOI: 10.1016/j.apcata.2012.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between catalytic and catalytic photo-assisted propene hydration by using supported heteropolyacid

Abstract: Hybrid materials have been prepared by impregnation of the heteropolyacid H 3PW 12O 40 on commercial TiO 2. The polyoxometalates (POM) amount deposited was 15, 30, 50 and 70% with respect to the weight of the TiO 2 support. Moreover two samples containing a POM amount of 15, and 50% with respect to the weight of SiO 2 were also prepared for the sake of comparison. All prepared samples were efficient catalysts for the hydration of propene to 2-propanol in gas-solid regime at atmospheric pressure and at temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…The set-up of the system was reported elsewhere. 35 A porous glass septum in the inlet of the flow allowed to distribute homogeneously the gaseous mixture. The reactivity runs were carried out with 0.5 g of solid powder by simply dispersing it as a thin layer inside the photoreactor (the fixed bed height was ca.…”
Section: 44mentioning
confidence: 99%
See 2 more Smart Citations
“…The set-up of the system was reported elsewhere. 35 A porous glass septum in the inlet of the flow allowed to distribute homogeneously the gaseous mixture. The reactivity runs were carried out with 0.5 g of solid powder by simply dispersing it as a thin layer inside the photoreactor (the fixed bed height was ca.…”
Section: 44mentioning
confidence: 99%
“…[27][28][29] In a previous paper the catalytic and catalytic photo-assisted activity of the H 3 PW 12 O 40 POM supported on TiO 2 Evonik P25 and SiO 2 was studied and a beneficial role of the photocatalytically active support on the reaction rate was reported. 35 The contemporary presence of heat and UV light improved the activity of the POM supported materials for the propene hydration reaction and the catalytic photo-assisted reaction occurred at a higher rate than the catalytic one when the solid support was an irradiated semiconductor. In that case, the more significant increase of reactivity was justified by considering the ability of TiO 2 to transfer electrons from the conduction band to the activated POM* species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogenized HPA enhances the activity by acting as an electron scavenger, which results in a delay in the recombination of h + and e -pairs, [35] and by catalyzing the photodegradation of the substrate by means of HPA -, which can react with molecular oxygen or another electrophilic species [36] (see Figure 4). The Keggin-type HPA supported on TiO 2 has been the most studied photocatalyst.…”
Section: Hpa Supported On Different Oxidesmentioning
confidence: 99%
“…[36] and it is performed by an electron acceptor such as O 2 dissolved in the suspension or in the absence of O 2 by other electrophilic species. [37] In this microreview the reported literature on the use of HPA-based materials as heterogeneous photocatalysts for environmental purposes is presented, in particular for complete or partial oxidation or reduction of organic molecules.…”
Section: ·+mentioning
confidence: 99%